Determination of Factors Affecting Consumers’ Bulgur Consumption Preferences - Kayaoğlu, Ahmet; Gülmez, Yavuz Selim (My University, 2022)
This research aims to determine the factors affecting the bulgur consumption preferences of consumers. The research data were obtained by using a face-to-face survey technique from 401 individuals living in the city center of Mardin by convenience sampling. In the analysis of the data, explanatory factor analysis and descriptive statistics were used. According to the research findings, the participants consider food quality, marketing activities, physical properties, and taste-price factors in their bulgur consumption preferences. According to the demographic characteristics of the participants, bulgur consumption preferences differ significantly. These; Taste-price according to a different gender, occupation, and the number of individuals in the household, food quality according to different marital status groups, food quality and marketing activities according to different education levels, marketing activities according to different household income groups. There was no significant difference between the groups according to the age variable.